Mechanistic study of the antibacterial potential of the prenylated flavonoid auriculasin against Escherichia coli. Issue 12 (27th August 2022) - Mohamed, Malik S.; Abdelkader, Karim; Gomaa, Hesham A. M.; Batubara, Afnan S.; Gamal, Mohammed; Sayed, Ahmed M.
Abstract: Bacterial resistance is spreading in an alarming manner, outpacing the rate of development of new antibacterial agents and surging the need for effective alternatives. Prenylated flavonoids are a promising class of natural antibiotics with reported activity against a wide range of resistant pathogens. Here, a large library of natural flavonoids (1718 structures) was virtually screened for potential candidates inhibiting the B‐subunit of gyrase (Gyr‐B). Twenty‐eight candidates, predominated by prenylated flavonoids, appeared as promising hits. Six of them were selected for further in vitro antibacterial and Gyr‐B enzyme inhibitory activities. Auriculasin is presented as the most potent antibacterial candidate, with a MIC ranging from 2 to 4 µg/ml against two clinically isolated multidrug‐resistant Escherichia coli strains. Mechanistic antibacterial analysis revealed auriculasin inhibitory activity towards the Gyr‐B enzyme on the micromolar scale (IC50 = 0.38 ± 0.15 µM). Gyr‐B interaction was further detailed by conducting an isothermal titration calorimetric experiment, which revealed a competitive inhibition with a high affinity for the Gyr‐B active site, achieved mostly through enthalpic interactions (Δ G binding = −10.69 kcal/mol). Molecular modeling and physics‐based simulations demonstrated the molecule's manner of fitting inside the Gyr‐B active site, indicating a very potential nucleus for the future generation of more potent derivatives. To conclude, prenylated flavonoids are interesting antibacterial candidates with anti‐Gyr‐B mechanism of action that can be obtained from a plant‐derived flavonoid. Abstract : A library of natural flavonoids (1718 structures) was virtually screened for potential inhibitors of the B‐subunit of gyrase (Gyr‐B), resulting in 28 promising hits, mainly prenylated flavonoids. Six of them were selected for further in vitro antibacterial and Gyr‐B enzyme inhibitory activities. Auriculasin was found to be the most potent antibacterial candidate against two clinically isolated multidrug‐resistant Escherichia coli strains.